Accelerated recovery program for patients after laparoscopic correction of pelvic organ prolapse: A prospective study - Yulia E. Dobrokhotova; Irina A. Lapina; Anatoly G. Tyan; Vladislav V. Taranov; Tatiana G. Chirvon; Nikita V. Glebov; Olesya V. Kaykova; Anastasiya A. Malakhova; Valeriia M. Gomzikova; Vladislava I. Klaushuk (IP Berlin A.V., 2023)
Pelvic organ prolapse belongs to the group of multidisciplinary pathological processes, in the pathogenesis of which various etiological components are involved, leading to destabilization of ligaments and muscular-fascial system. In most cases, pelvic floor dysfunction requires surgical treatment, which allows eliminating defects and reducing clinical symptoms, also improving quality of life of patients. Performing surgeries for genital prolapse using laparoscopic approach is associated with high efficiency and low risk of unfavorable clinical outcomes. However, despite significant progress and improvement of surgical treatment options, the choice of the rational treatment in terms of a personalized approach remains relevant. This literature review analyzes classical and alternative modes of laparoscopic correction of pelvic organ prolapse.